"It's been worth it" : the experiences of employed caregiving fathers : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Auckland, New Zealand - Bethune, Danielle Sian (Massey University, 2020)
An increasing number of men are in caregiving roles, yet the overwhelming majority of research at the work-family interface has focused on women’s experiences, with little attention having been paid to men’s. Interpretative Phenomenological Analysis was used to analyse the accounts of eight caregiving fathers to explore the experiences of men who have altered their working arrangements to care for their children. This resulted in rich, detailed knowledge about their experiences and produced two broad themes. The first theme The Caregiving Father was about participants’ experiences entering and being located in a caregiving role. Men became caregiving fathers as an outcome of a range of interrelated factors shaped by social forces. Once in the role, they experienced a complex interplay in their masculine identities, suggesting that although hegemonic masculinity and fathering norms are expanding to be more inclusive of caregiving, breadwinning expectations and the norms around the ideal worker still linger. The second theme Work Factors was about work characteristics that influenced the management of caregiving fathers’ work, careers and caregiving commitments. Participants’ access to flexible working arrangements was highly dependent on the extent to which their employer valued them both professionally and personally. Work-life balance decisions and experiences were clearly impacted by their organisations’ generally strong work-family cultures. Caregiving fathers appeared to exist in a paradox where they were not discriminated in hiring and progression opportunities, although taking advantage of progression opportunities necessitated the relinquishment of their flexibility to some extent. Overall, these fathers found that benefits associated with their caregiving roles outweighed any negative impacts, and highlighted the value of acknowledging individuals’ self-direction in their careers, the role of social forces in shaping these, and that career success can be subjectively determined.
Keywords: 520502 Gender psychology